2007
DOI: 10.1063/1.2432290
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence study of an ultrathin strained silicon on insulator layer

Abstract: Low temperature photoluminescence has been performed in order to analyze the strain effect on the Si band structure for an 8 nm thick tensile strained silicon layer on insulator. The authors show three phonon assisted optical transitions related to the strained silicon top layer at 0.923, 0.983, and 1.022eV. The 0.983eV line of the TO phonon assisted transition corresponds to a 115meV strain induced band gap shrinkage at Δ point which agrees with the calculated values of strained silicon band gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…As a consequence, silicon (Si) indirect bandgap shrinkage is caused by the strain induced in the silicon layer; this effect predicted by theoretical calculation [4][5][6] has been confirmed in the previous works by low temperature photoluminescence. [7][8][9] In this work, we report a photoluminescence study in order to evaluate the temperature dependence of the sSi indirect bandgap between 9 and 300 K with particular attention on the low temperature range (below 100 K). Even if these measurements may seem unnecessary for room temperature in CMOS technological application, they are fundamental for the understanding and the modelling of strained silicon on insulator (sSOI) electrical properties such as free carrier densities and mobilities extraction from temperature Hall measurements, for instance.…”
mentioning
confidence: 99%
“…As a consequence, silicon (Si) indirect bandgap shrinkage is caused by the strain induced in the silicon layer; this effect predicted by theoretical calculation [4][5][6] has been confirmed in the previous works by low temperature photoluminescence. [7][8][9] In this work, we report a photoluminescence study in order to evaluate the temperature dependence of the sSi indirect bandgap between 9 and 300 K with particular attention on the low temperature range (below 100 K). Even if these measurements may seem unnecessary for room temperature in CMOS technological application, they are fundamental for the understanding and the modelling of strained silicon on insulator (sSOI) electrical properties such as free carrier densities and mobilities extraction from temperature Hall measurements, for instance.…”
mentioning
confidence: 99%
“…However, confocal microscopy analysis is a promising tool to estimate the response of nanometric materials under ionizing radiation. The experimental setup will be improved to enhance the detection of each component of complex stacked samples notably by striking the device with various excitation wavelength, by using infrared detectors and by varying the temperature used during the experiments [15,28]. …”
Section: Resultsmentioning
confidence: 99%
“…Moutanabbir et al [14] and Munguia et al [15] reported mechanical stress measurements in thin strained Silicon-OnInsulator (sSOI) layers using Raman and photoluminescence spectroscopy.…”
Section: Confocal Microscopy Measurementsmentioning
confidence: 99%
“…A more recent study of 8 nm thick tensile strained SOI explored in detail the effects of strain on the low temperature photoluminescence from strained Si [60]. While this study was not focused on increasing the luminescence efficiency from Si it presents an interesting technique for quantifying the strain present in devices which leverage strain to enhance optical activity.…”
Section: Strained Simentioning
confidence: 99%
“…Also, how can we quantify this strain? It has not given rise to signatures in PL spectra, as in [60]. Can we enhance this strain effect until it is clearly playing a role in the luminescence?…”
Section: Synthesis Of Techniquesmentioning
confidence: 99%